Search Activities, Cost of Living and Local Labor Markets - Eleonora Patacchini; Yves Zenou (The Research Institute of Industrial Economics (IUI), 2003)
A model is considered in which optimal search intensity is a result of a trade off between short run losses due to higher search costs (more interviews, commuting...) and long-run gains due to a higher chance of finding a job. We show that this optimal search intensity is higher in areas characterized by larger cost of living and/or higher labor market tightness. This model is then tested for England on sub-regional data. We estimate a spatial error model and we find that both the local cost of living and the local labor market tightness are found to have a positive and significant effect on unemployed average search intensity. These findings are consistent with the prediction of the theoretical model.
Keywords: C21; J64; R10; 330; Job Matching; Search Intensities; Spatial Correlation; Suchtheorie; Arbeitsuche; Schätzung; Verbraucherpreisindex; Großbritannien